Similar Bronchodilation with Formoterol Delivered by Aerolizer or Turbuhaler. Issue 5 (3rd October 1999) - Lötvall, J; Mellén, A; Arvidsson, P; Palmqvist, M; Radielovic, P; Kottakis, J; Pfister, P
Abstract : BACKGROUND: In many countries, two dry powder formulations of inhaled formoterol are available for clinical use; one uses a single-dose device (Foradil, Aerolizer), and the other uses a multiple-dose device (Oxis, Turbuhaler). OBJECTIVES: To study the bronchodilating effect of formoterol 12  μ g when delivered via the Aerolizer and Turbuhaler devices over 12 h. STUDY DESIGN: Randomized, double-blind, placebo controlled crossover study. Forced expiratory volume in one second (FEV1 ) was monitored during a 12 h period. PATIENTS: Nineteen nonsmoking asthma patients were included in the trial on the basis of reversibility of symptoms in response to inhaled salbutamol (either 200 or 400  μ g given cumulatively; minimum reversibility 15%). RESULTS: There were no significant differences between the two dry powder devices regarding the change from baseline of FEV1 over 12 h, the area under the curve of FEV1 over 12 h or the maximum value of FEV1 . The improvement in FEV1 with formoterol 12  μ g versus placebo was highly significant for both devices. CONCLUSIONS: Formoterol is similarly effective when used as a dry powder when given by either Aerolizer or the Turbuhaler.